Chlorhexidine–thymol varnish as an adjunct to scaling and root planing: A clinical observation - Vishal Anand; Vivek Govila; Minkle Gulati; Bhargavi Anand; Rajesh Jhingaran; Pavitra Rastogi (Journal of Oral Biology and Craniofacial Research)
Aim: To evaluate the efficacy of chlorhexidine–thymol varnish (Cervitec Plus®) as an adjunct to scaling and root planing in the improvement of periodontal parameters. Material and methods: A split mouth randomized clinical trial was conducted in 25 subjects with chronic periodontitis receiving scaling and root planing alone and as an adjunct to chlorhexidine–thymol varnish (Cervitec Plus®) and chlorhexidine–thymol varnish (Cervitec Plus®) alone. Clinical examinations were performed at baseline, 1 month and 3 months. Results: Short term advantages were observed in the clinical parameters in subjects receiving scaling and root planing and an adjunct, chlorhexidine–thymol varnish (Cervitec Plus®) who showed the greatest improvement in the periodontal parameters at 3 months. Conclusion: Subjects with chronic periodontitis significantly benefit from scaling and root planing when used with an adjunct, chlorhexidine–thymol varnish (Cervitec Plus®).